The Influence of the Activeness of Following Instagram @Ngajilagi.id on Interest in Reading the Qur'an in Indonesia - Malik, Asriati Aulia (Islamic Religious Education Departement, 2024)
This study aimed to assess the extent of interest in reading the Quran among @ngajilagi.id followers, the level of engagement of Instagram users with the @ngajilagi.id account, and whether there's a correlation between interest in Quranic reading and Instagram activity among followers in Indonesia. This research adopted a quantitative ex-post facto approach, employing targeted sampling and simple linear regression analysis for hypothesis testing. The findings indicate a substantial level of interest in Quranic reading in Indonesia. The study revealed that 4% fell within the deficient category, 21% in the low category, 29% in the medium category, 36% in the high category, and 10% in the very high category. Regarding Instagram activity on @ngajilagi.id in Indonesia, it was moderate. The analysis indicated that 8% fell within the deficient category, 21% in the low category, 38% in the mild category, 23% in the high category, and 10% in the very high category. Based on the analysis and data processing conducted by the researchers, it was found that the significance value is 0.000 < 0.05. This indicates that the null hypothesis (H0) is rejected, and the alternative hypothesis (H1) is accepted. Therefore, it can be concluded that the activity of followers of the Instagram account @ngajilagi.id influences the interest in reading the Qur'an in Indonesia, with an influence of 24.7%.